PENGARUH RISK PREFERENCE, ARTICLE PREFERENCE, DAN GENDER TERHADAP INVESTMENT DECISION DENGAN CONFIRMATION BIAS SEBAGAI VARIABEL MEDIASI - Tri Nuryanti; Dina Yeni Martia; Rahima Norma Ariestaputri; Alfa Lailatula Merdeka Wati; Nurul Widianti; Suci Rahma Andari (Jurnal Akuntansi Trisakti, 2025)
This study aims to analyze the influence of Risk Preference, Article Preference, and Gender on Investment Decision-Making, with Confirmation Bias as a mediating variable. The research was conducted among students of Politeknik Negeri Semarang, representing a young generation with high digital literacy and a tendency toward cognitive biases. A quantitative approach was applied using an online survey with 116 respondents, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that Risk Preference significantly affects both Confirmation Bias and Investment Decision, while Article Preference only affects Confirmation Bias. Gender shows no significant influence on either variable. Furthermore, Confirmation Bias plays a mediating role between Risk Preference and Investment decisions, but not between Article Preference or Gender and investment decisions. These findings highlight that psychological factors, especially risk tolerance and the tendency to favor information aligned with existing beliefs, are more influential in shaping investment decisions than demographics or content preferences. Confirmation Bias functions as a psychological mechanism that amplifies the influence of risk behavior on financial decision-making. Therefore, financial literacy programs should integrate behavioral and psychological components to foster more rational decision-making among young investors. Future studies are encouraged to expand the respondent base beyond students and explore other psychological factors such as overconfidence, herding behavior, or loss aversion to gain deeper insights into the behavioral dynamics of investment decisions.